1989
DOI: 10.1149/1.2096706
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Class of Organosulfur Electrodes for Energy Storage

Abstract: A broad class of organosulfur compounds is discussed which may offer unique advantages as positive storage electrodes in advanced battery systems. The organosulfur electrodes operate between ambient and 150~ are inexpensive, and inert to many metals. In addition, the physicochemical and electrochemical properties of the organosulfur electrodes may be varied in a predictable way. At room temperature these materials may be crystalline, liquid, or polymeric. Batteries based on the novel organosulfur positive elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
93
0

Year Published

1990
1990
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 137 publications
(93 citation statements)
references
References 8 publications
0
93
0
Order By: Relevance
“…Among those organodisulfide compounds, 2,5-dimercapto-1,3,4-thiadiazole (DMcT) is one of the most promising materials since it possesses high theoretical specific capacity and high stability to temperature [9,10]. However, the application of the DMcT has been hindered due to its poor electrically conductivity and low redox rate at room temperature [11].…”
Section: Introductionmentioning
confidence: 99%
“…Among those organodisulfide compounds, 2,5-dimercapto-1,3,4-thiadiazole (DMcT) is one of the most promising materials since it possesses high theoretical specific capacity and high stability to temperature [9,10]. However, the application of the DMcT has been hindered due to its poor electrically conductivity and low redox rate at room temperature [11].…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, DMcT shows slow redox kinetics and poor electrical conductivity at room temperature. Therefore it requires accelerated redox kinetics by electrocatalysis for commercial application [1,2]. Recently, it has been reported that the redox performance of DMcT can be improved by electrocatalysts such as polyaniline (PAn) and polypyrrol (PPy).…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14] A series of compounds having -SH groups are thought to have a significant potential as energy storage materials, whereby energy exchange occurs according to a reversible polymerization-depolymerization process (2 SH ↔ S-S). 1,2 Among these compounds, 2,5-dimercapto-1,3,4-thiadiazole (DMcT) was first studied by Visco and co-workers 6 as an active cathode material for lithium secondary batteries.…”
Section: Introductionmentioning
confidence: 99%